Great cormorants and grey herons depredating at finfish aquaculture: Factors affecting the human–wildlife conflict - Ekblad, Camilla; Westerbom, Mats; Laaksonen, Toni; Kankainen, Markus; Ovaskainen, Antti; Sinisalo, Suvi; Jormalainen, Veijo (Springer Nature, 2025)
Sustainable aquaculture requires consideration of its interactions with wildlife. Human–wildlife conflicts arise when piscivorous birds, such as cormorants and herons, depredate in fish farms. By surveillance cameras, we quantified the depredation pressure of birds at fish farms along the Finnish coast. The pressure varied considerably between farms, from no bird visits to daily losses of hundreds of fish. Grey herons were most numerous and depredated 2–5 times more fish than cormorants, which are commonly regarded bigger threats. Depredation rates decreased with the increasing fish size even though cormorants also took large fish. Piscivorous raptors seldom foraged in farms but were interested in larger fish. Proximity to bird breeding colonies did not affect the predation pressure. Protective nets were effective against raptors and cormorants, but grey herons used them as depredation platforms. Knowledge on factors explaining depredation rates is valuable for science-based planning of measures to mitigate the human–wildlife conflict.